Pengaruh Service Quality, Perceived Value, dan Service Innovation Terhadap Customer Satisfaction Nasabah Bank BCA di Kota Surabaya - Tarishah Zahmita Davina Haryono; Basuki Rachmat; Harry Widyantoro; Trisa Indrawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
In increasingly tight competition, innovation in service quality in the banking sector is needed now to increase customer satisfaction and be able to compete with other banks. Banks that are able to adapt to customer needs through implementing the latest innovations tend to have an advantage over other banks. This research was conducted to examine the influence of service quality, perceived value, and service innovation on customer satisfaction of BCA Bank customers in Surabaya. This research is quantitative in nature with non-probability sampling, namely judgment sampling. Respondents in this study were BCA Bank customers whose characteristics were at least 17 years old, BCA Bank customers for at least 1 year, BCA Bank savings customers, and had used BCA Bank services at least once in the last 3 months. The sample consisted of 339 respondents with data collection techniques through questionnaires. This research uses Structural Equation Modeling (SEM) on Partial Least Square (PLS) using SmartPLS version 4. The results of this research show that there is a positive and significant influence on service quality, perceived value, and service innovation on customer satisfaction.